Biomarkers and C and S Isotopes of the Permian to Triassic Solid Bitumen and Its Potential Source Rocks in NE Sichuan Basin. (13th August 2017) - Cai, Chunfang; Xu, Chenlu; He, Wenxiang; Zhang, Chunming; Li, Hongxia
Abstract : The potential parent source rocks except from Upper Permian Dalong Formation (P3 d) for Upper Permian and Lower Triassic solid bitumen show high maturity to overmaturity with equivalent vitrinite reflectance (E R o ) from 1.7% to 3.1% but have extractable organic matter likely not contaminated by younger source rocks. P3 d source rocks were deposited under euxinic environments as indicated by the pyrite δ 34 S values as light as - 34.5 ‰ and distribution of aryl isoprenoids, which were also detected from the Lower Silurian (S1 l) source rock and the solid bitumen in the gas fields in the west not in the east. All the solid bitumen not altered by thermochemical sulfate reduction (TSR) has δ 13 C and δ 34 S values similar to part of the P3 l kerogens and within the S1 l kerogens. Thus, the eastern solid bitumen may have been derived from the P3 l kerogens, and the western solid bitumen was likely to have precracking oils from P3 l kerogens mixed with the S1 l or P3 d kerogens. This case-study tentatively shows that δ 13 C and δ 34 S values along with biomarkers have the potential to be used for the purpose of solid bitumen and source rock correlation in a rapidly buried basin, although further work should be done to confirm it.